Acidosis and Phosphate Directly Reduce Myosin’s Force-Generating Capacity Through Distinct Molecular Mechanisms - Woodward, Mike; Debold, Edward P. (Frontiers in Physiology, 2018)
Elevated levels of the metabolic by-products, including acidosis (i.e. high [H+]) and phosphate (Pi) are putative agents of muscle fatigue, however the mechanism through which they affect myosin’s function remain unclear. To elucidate these mechanisms, we directly examined the effect of acidosis (pH 6.5 vs. 7.4), alone and in combination with elevated levels of Pi on myosin’s force generating capacity in a three-bead laser trap assay. Acidosis decreased myosin’s average force-generating capacity by 20% (p<0.05). The reduction was due to both a decrease in the force generated during each actomyosin interaction, as well as an increase in the number of binding events generating negative forces. Adding Pi to the acidic condition resulted in a quantitatively similar decrease in force but was solely due to an elimination of all high force-generating events (>2pN), resulting from an acceleration of the myosin’s rate of detachment from actin. Acidosis and phosphate also had distinct effects on myosin’s steady-state ATPase rate with acidosis slowing it by ~90% (p>0.05), while the addition of Pi under acidic conditions caused a significant recovery in the ATPase rate. These data suggest that these two fatigue agents have distinct effects on myosin’s cross-bridge cycle that may underlie the synergistic effect that they have muscle force. Thus these data provide novel molecular insight into the mechanisms underlying their depressive effects of Pi and H+ on muscle contraction during fatigue.